A luminescent cerium metal–organic framework for the turn-on sensing of ascorbic acid. Issue 81 (28th September 2017) - Yue, Dan; Zhao, Dian; Zhang, Jun; Zhang, Ling; Jiang, Ke; Zhang, Xin; Cui, Yuanjing; Yang, Yu; Chen, Banglin; Qian, Guodong
Abstract : Based on a simple redox reaction, the cerium metal–organic framework (ZJU-136-Ce) exhibits highly sensitive and selective turn-on sensing of AA. Abstract : We report a cerium metal–organic framework (ZJU-136-Ce) for the turn-on fluorescence sensing of AA. The fluorescence enhancement is attributed to the specific redox reaction between AA and Ce 4+ . The detection limit of AA reaches 7 nM, showing its potential for AA detection in the environmental industry and clinical medicine.